t-pebbling property satisfies the C_5×C_5×C_5 Graph - et. al., Jitendra Binwal, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
A graph pebbling is mathematical game play on the vertices of graph with respect to the pebbling steps. The pebbling step is the shifting of two pebbles and attachment of one pebble on the specified arbitrary vertex. The -pebbling number of the graph, is the maximum of over all the vertices of where, is the pebbling number of a vertex . We propose the pebbling number of where graph is with vertices.